Noor's Curve, a New Geometric Form of Agnesi Witch, a Construction Method is Produced (Baghdad Science Journal, 2021)
In this paper, a new form of 2D-plane curves is produced and graphically studied. The name of my daughter "Noor" has been given to this curve; therefore, Noor term describes this curve whenever it is used in this paper. This curve is a form of these opened curves as it extends in the infinity along both sides from the origin point. The curve is designed by a circle/ ellipse which are drawing curvatures that tangent at the origin point, where its circumference is passed through the (0,2a). By sharing two vertical lined points of both the circle diameter and the major axis of the ellipse, the parametric equation is derived. In this paper, a set of various cases of Noor curve are graphically studied by two curvature cases; a circle and an ellipse, and all figures and obtained rigour measurements are checked by AutoCAD program. With its simple, symmetric form, the future predictions are tuned for the Noor's curve to be usefully engaged in important practical applications.